Mantenimiento y Puesta en Marcha de un Banco Didáctico para Entrenamiento en Electrohidráulica. (2023)
The present project on maintenance and commissioning electrohydraulic test bench automation laboratory se developed at the Antonio University Nariño headquarters Valledupar, in addition to the own resources, with the help of others projects that also worked with test benches, as well as knowledge learned about theories on the subject of electrohydraulics and work experience gained in companies. The purpose of this project was to make the bank available for use by college students, to ensure the good performance of the himself, contribute to his training and achieve that they appropriate knowledge through practice, to help them develop industry skills electrohydraulic. ​Search details Post comments side panels